FACTOR STRUCTURE ALL-AROUND OFF STUDENTS THE PHYSICAL EDUCATION AND SPORTS - Ratko PAVLOVIĆ; Martin PUPIŠ; Simeonov, Aleksandar; Snezana BOROVČANIN; Milan CUROVIĆ (Slovak Journal of Sport Science, 2018)
All-around competition is the only competition in which it does not matter whether the athlete is the first, the second or the last in a discipline. What matters is the total number of points, and a rounder competes against his/her personal capabilities and standards. Athletic all-around competitions are a series of consecutive athletic competitions divided in two days. Success is calculated by the sum score of all disciplines that are pointed due to the international athletic tables. The research included a group of 60 students of the Faculty of Physical Education and Sport in East Sarajevo, male, age 20±0,5 years. The aim of this study was to determine the structure of athletic all-around competition, respectively all-around competition type of students and dominance of individual disciplines. In athletic all-around competition were represented a total of 8 (eight) disciplines. Using factor analysis in a defined area were gained two factors (all-round type) with a total of explained 78% of variance of the set. The first factor (type) has exhausted 60% of the common variance of the set and is defined as all-round type of runner-jumper. Another factor has exhausted about 18% of the analyzed set and is defined as throwing type of students (latent dimension of power). The obtained results of the research are partially in contrast with similar research on a sample of top athletes.
Keywords: athletic all-around competition; the structure; students...